2020
DOI: 10.1186/s40662-020-00186-3
|View full text |Cite
|
Sign up to set email alerts
|

Decentration and tilt of plate-haptic multifocal intraocular lenses in myopic eyes

Abstract: Background: To investigate the decentration and tilt of plate-haptic multifocal intraocular lenses (MfIOLs) in myopic eyes. Methods: Myopic (axial length [AXL] > 24.5 mm) and non-myopic (21.0 mm < AXL ≤ 24.5 mm) cataract eyes were enrolled in this prospective study and randomly assigned to receive implantation of Zeiss AT LISA tri 839MP lenses (Group A) or Tecnis ZMB00 lenses (Group B). In total, 122 eyes of 122 patients were available for analysis. Decentration and tilt of MfIOLs, high-order aberrations (HOAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
2
26
0
1
Order By: Relevance
“…Because AXL was similar in the two IOL groups in our study (p = 0.6400), we believe that the differences between groups in the refractive and visual outcomes are not attributable to this anatomical parameter. IOL decentration and tilt were not measured in our study, although both the Liberty and AT LISA tri IOLs have been reported to undergo some decentration following implantation [24,39]. IOL decentration can affect refractive and visual outcomes [38,40].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Because AXL was similar in the two IOL groups in our study (p = 0.6400), we believe that the differences between groups in the refractive and visual outcomes are not attributable to this anatomical parameter. IOL decentration and tilt were not measured in our study, although both the Liberty and AT LISA tri IOLs have been reported to undergo some decentration following implantation [24,39]. IOL decentration can affect refractive and visual outcomes [38,40].…”
Section: Discussionmentioning
confidence: 71%
“…The explanation for the better refractive predictability of the Liberty IOL is also unclear. Comparing two MFIOLs, Meng et al reported that a plate haptic lens had better positional stability in the capsular bag than a lens with a C-loop haptic in myopic eyes (AXL > 24.5 mm) and noted no differences in non-myopic eyes (21.0 mm < AXL ≤ 24.5 mm) [39]. Because AXL was similar in the two IOL groups in our study (p = 0.6400), we believe that the differences between groups in the refractive and visual outcomes are not attributable to this anatomical parameter.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Underlying reasons for this early rotation might be remaining OVD behind the IOL, myopia and concomitant greater capsular bag size 18 but also insufficient IOL-capsulorhexis overlap (<0.5 mm). 5,6,19 In our study, the use of different OVDs for filling the capsular bag did not have an impact on the rotation stability. Overall, only in one IOL, rotation exceeded 10.0 degrees within one day of surgery (EoS vs. 1 day).…”
Section: Discussionmentioning
confidence: 47%
“…This is in agreement with the recent findings of Meng et al who compared C-loop haptics and plate-haptics within myopes and non-myopes in terms of tilt and decentration. 6 While platehaptics were more stable in myopic eyes, there was no increase of tilt and decentration with greater axial length within this group.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation